Growth Retardation in Children: How to Face? - Islam, Mohammad Imnul (Bangladesh Journal of Medicine, 2024)
Growth is an irreversible constant increase in the size of organs and the body from fetal to adulthood. It is positively influenced by parental health, genetic, nutrition, hormonal, and environmental factors.1-3 Growth can be assessed by proper history taking, accurate measurement of growth parameters, determination of growth percentile and trajectory for age and sex.4 According to WHO, weight, height, and head circumference are used for growth assessment of children < 2 years, whereas weight, height, and BMI are used for children>2 years. 4,5 Growth of children will be retarded if their height is more than 2 standard deviations below the mean (3rd percentile) or marked decrease in growth velocity.7 Growth retardation is a burning issue of global health and stunting acts as the most prevalent indicator of child growth failure.In South Asia, the higher prevalence of growth failure was evidenced by 28.6% of global stunting in India and 6.8% in Pakistan.8 In 2017, the prevalence of stunting in Bangladeshi children was 31%, which become 24% in 2022.9 Like other lower middle-income countries, Bangladesh faces a great challenge to achieve growth due to poor socioeconomic conditions, malnutrition, inadequate health care access, poor maternal education, and poor ability of care giving.10 Delayed evaluation and detection of underlying causes make an obstacle in achieving targeted growth in adulthood, increase morbidity, and have far-reaching effects on psychological well-being. Lack of caregivers' knowledge, the disparity between necessity and financial support, less prioritization, and the communication gap between the health service providers and users still become principal issues in the early assessment and detection of growth failure in children of Bangladesh.11 Timely action is now required to combat this challenge and ensure the proper growth of future generations of this nation. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 145